EKSISTENSI KEBUDAYAAN SUKU DAYAK NGAJU DI KECAMATAN MARIKIT KABUPATEN KATINGAN - Basirun; Normuslim; Muslimah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study aims to examine how the Dayak Ngaju community in Marikit District, Katingan Regency, maintains the sustainability of its culture amid the pressures of modernization and globalization. The research specifically focuses on the forms of cultural preservation, adaptation strategies, and factors that support or hinder the continuity of Dayak Ngaju cultural practices. This study employed a qualitative approach, with data collected through observation, in-depth interviews, and documentation. The findings show that the sustainability of Dayak Ngaju culture is reflected in the continued implementation of traditional rituals, the active use of the Dayak Ngaju language in daily communication, and the transmission of cultural values through customary activities involving both elders and younger generations. However, the study also identifies several challenges, including declining youth participation in traditional practices, the growing influence of external cultures, and the lack of systematic cultural documentation to support long-term preservation. Despite these challenges, cultural sustainability continues to be supported by the role of traditional leaders, informal cultural education within families, and limited government initiatives in cultural preservation. This study contributes by identifying community-based cultural preservation practices and the main factors influencing the sustainability of Dayak Ngaju culture, while emphasizing the importance of strengthening intergenerational cultural transmission to preserve local cultural identity in the long term.